Evaluating the solar resource potential on different tracking surfaces in Nigeria - Okoye, Chiemeka Onyeka; Bahrami, Arian; Atikol, Ugur (Pergamon-Elsevier Science Ltd, 2018)
In this study, the available solar potential of some selected locations in Nigeria on an inclined, single-axis (considering 6 tracking orientations) and dual-axis tracking surfaces are assessed using hourly radiation data. More accurate and widely validated Perez anisotropic and Koronakis isotropic models are adopted in the estimation of the diffuse component of the radiation on an inclined surface before integrating trackers. The method utilized in the simulation are compared and verified by the result from System Advisor Model (SAM) before carrying out the detail resource assessment. The annual solar resource potential for the locations on a fixed surface inclined at an optimal angle ranges from 1621 to 2279 kW h m(-2), with the use of solar trackers; the yield would vary from 1664 to 2983 kW h m(-2). This amount of energy, if fully harnessed, would not only help in narrowing the gap between energy demand and supply but also would make a significant contribution in enriching the energy generation mix of the country. The increase in the annual energy yield of the dual-axis tracker compared to the other trackers and fixed tilted at optimal angle orientations ranged from 1.86% to 31.52%. Overall, the study is expected to provide a practical guide to aid designers and installers in the selection and implementation of suitable solar trackers in the country.
Keywords: Solar radiation; Optimum tilt angle; Tracking system; Nigeria; Performance ranking